Analisis Pengaruh Fasilitas Pariwisata Terhadap Kesempatan Kerja Dan Jumlah Wisatawan Di Indonesia - Ilham fadhillah yuskal; Sri Ulfa Sentosa (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the influence of tourism facilities on employment opportunities and the number of tourists in Indonesia from 2017 to 2021. Quantitative research type. The object of this research was carried out in all provinces in Indonesia for the period 2017 to 2021. The type of data used is secondary data that researchers obtained from the Central Statistics Agency (BPS) of Indonesia. The data analysis method used is simultaneous panel data regression, with the chow test, hausman test and hypothesis test (F test, and t test), the simultaneous panel data regression estimation model used is the Common Effect Model, data processing using the E-Views 10 program. The results of this study indicate that together the variables (1) number of tourists, hotels and restaurants do not have a significant effect on employment opportunities in Indonesia. (2) employment opportunities, tourist attractions and tourism costs have a significant effect on the number of tourists in Indonesia. Partially: (3) hotels have a positive and significant effect on employment opportunities in Indonesia. (4) restaurants also have a positive and significant effect on employment opportunities in Indonesia. (5) The number of tourists shows a positive and significant effect on employment opportunities in Indonesia. (6) Tourist attractions have a positive but not significant influence on the number of tourists in Indonesia. (7) Tourism costs have a negative and significant influence on the number of tourists in Indonesia. (8) Job opportunities have a positive and significant impact on the number of tourists in Indonesia.